Minimum wages, minimum labour costs and the tax treatment of low-wage employment - Herwig Immervoll (Institute for the Study of Labor (IZA), 2007)
International comparisons of minimum-wage levels have largely focused on the gross value of minimum wages, ignoring the effects of taxation on both labour costs and the net income of employees. This paper presents estimates of the tax burdens facing minimum-wage workers. These are used as a basis for cross-country comparisons of the net earnings of these workers as well as the cost of employing them. In addition, results show the evolution of net incomes and labour costs during the 2000-2005 period and the relative importance of minimum-wage adjustments and tax reforms in driving these changes. Statutory minimum wages are in place in 21 OECD countries, ranging between USD 0.7 and USD 10 per hour. In a number of countries, minimum-wage levels have gone up in real terms in recent years. Given considerable tax burdens even at the lowest wage levels, tax policy measures can have a sizable impact on the net earnings available to low-wage workers. Social contributions and payroll taxes add, on average, around 18% to the cost of employing minimum-wage workers. The international variation of minimum labour costs in dollar terms is enormous, with hourly costs in the highest-cost country (the Netherlands) exceeding those at the bottom (Mexico) by a factor of 12. Differences are also large when compared across countries that are closer geographically or whose economies are more integrated. Despite reductions in non-wage labour costs in several countries, there has been no convergence of minimum labour costs in recent years. This paper is the working paper version of a chapter to appear in the 2007 edition of Taxing Wages, an annual OECD publication. The Taxing Wages chapter will include results for 2006.
urn:nbn:de:101:1-20080425411
Keywords: 330; Mindestlohn; Lohnsteuer; OECD-Staaten